Study on the Mechanism of Particle Breakage under New Composite Loads - Zhanfu Li; Yiqing Ye; Xin Tong; Kunyuan Li (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
A theoretical model of particle breakage under a novel combination of dynamic and static loads is presented in this paper. In order to enhance the capability of the actual physical and mechanical properties towards rocks, parallel connector parameters of a bonded particle model (BPM) from the discrete element method (DEM) were investigated by uniaxial compression tests. Then, the efficiency evaluation index system of particle breakage was defined and different simulations of various parameters were set, i.e. the speed of the moving plate, the curvature of the moving plate, the curvature of the fixed plate, the space between the two plates, and the initial particle radius. The mechanism of particle breakage was analyzed by the relationships between the efficiency evaluation index and various parameters. The investigation of particle breakage theory and law can help to design and improve crushing equipment, reduce the energy consumption of the crusher, and improve the quality of the broken product.